(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Nonlinear regression is a form of regression analysis in which data is fit to a model and then expressed as a mathematical function. Simple linear regression relates two variables (X and Y) with a straight line (y = mx + b), while nonlinear regression relates the two variables in a nonlinear (curved) relationship. The goal of the model is to make the sum of the squares as small as possible